Sistem Pendukung Keputusan Pemilihan Penerima Bantuan Sosial Menggunakan Metode Simple Additive Weighting - Rifasya, Pramadika; Aryanti, Utami; Anwar, Moh. Taufan; Atmoko, Dwi (Jurnal Dimamu, 2024)
Social assistance (bansos) is one form of government program that has become the main instrument in supporting the welfare of low-income communities in Cilaengka Wetan Village to meet their basic needs. However, the main challenge in implementing this program is the selection process for aid recipients which is often done manually, so that it risks causing inaccuracy and injustice in determining recipients. This study aims to develop a Decision Support System (DSS) for the selection of social assistance recipients in Cicalengka Wetan Village using the Simple Additive Weighting (SAW) method so that social assistance recipients are right on target and ensure that assistance is given to people who really need it. The Simple Additive Weighting (SAW) method was chosen because it is able to perform criteria-based calculations with objective and transparent results. The trial results show that the developed system can provide valid recommendations and is in accordance with the conditions of prospective recipients. This research assistance is expected to be a practical solution in social distribution, not only in Cicalengka Wetan Village but also in other areas with adjustment criteria. As a further development, an integration system with web-based technology or mobile applications can be carried out to improve the accessibility and efficiency of the decision-making process.